Adverse Events after Rigid and Flexible Endoscopic Repair of Zenker's Diverticula: A Systematic Review and Meta‐analysis. (23rd April 2019) - Crawley, Brianna; Dehom, Salem; Tamares, Shanalee; Marghalani, Abdullah; Ongkasuwan, Julina; Reder, Lindsay; Ivey, Chandra; Amin, Milan; Fritz, Mark; Pitman, Michael; Tulunay‐Ugur, Ozlem; Weissbrod, Philip
Abstract : Objective: To determine adverse events after endoscopic flexible vs endoscopic rigid cricopharyngeal myotomy for treatment of Zenker's diverticulum (ZD). Data Sources: Systematic review of MEDLINE, Web of Science, CINAHL, Clinicaltrials.gov, and Cochrane Central Register of Controlled Trials for all years according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Additional studies were identified from review citations and a by hand search of manuscripts referencing ZD. Review Methods: A structured literature search was conducted to identify studies for this systematic review. Methodological Index for Non‐randomized Studies (MINORS) criteria were applied to assess study quality. For inclusion, each study had to provide data for at least 10 adult patients who had undergone endoscopic ZD repair reporting clear association with the postprocedure course in each case. Data extracted included all reported adverse events, recurrences, follow‐up, and operative times. Results: In total, 115 studies were included. All but 8 were retrospective case series. Sixty‐one reported series of patients after rigid endoscopic stapler repair, 31 after rigid laser repair, and 13 with other rigid endoscopic instruments. Twenty‐nine flexible endoscopic studies were included. Mortality, infection, and perforation were not significantly more likely in either the rigid or the flexible group, but bleeding and recurrence were more likely after flexible endoscopic techniques (20% vs <10% and 4% vs 0%, respectively). Dental injury and vocal fold palsy were reported rarely in the rigid endoscopic groups. Conclusions: Adverse events are rare after endoscopic Zenker's repair. The flexible approach minimizes exposure limitations and can be completed in some patients without general anesthesia. Transoral rigid approaches result in fewer revision surgeries compared with flexible diverticulotomy.